Recent developments in durability of FRP-masonry systems - Ghiassi, Bahman (2013)
Fiber reinforced polymers (FRPs) are being more and more used for external strengthening of masonry structures. Therefore, characterization of the short and long-term behavior of bond between FRP composites and masonry substrates in a service environment is crucial for design purposes. A full body of experimental and theoretical investigations is required for durability assessment of FRP strengthened structures. However, most of the research in this area has been devoted to FRP-concrete specimens, and the available data for FRP- strengthened masonry components is still lacking. This paper presents recent experimental results of a large experimental campaign under development at the University of Minho. The aim is to characterize the short and long-term behavior of bond in FRP-strengthened masonry elements. Debonding tests have been performed on masonry bricks strengthened with different FRP materials for investigating the short-term aspects of the bond behavior. Accelerated ageing tests have been performed on FRP-strengthened masonry elements and the degradation of the bond due to environmental conditions is investigated. The environmental conditions consist of the coupling effect of temperature cycles and relative humidity. The degradation of bond has been measured by performing conventional single-lap shear bond tests.